Disentangling entanglement in Cape fur seals for better management of plastic pollution impacts - Winroth, Forsberg Sara Trine (Department of Biological Sciences, 2024)
Marine litter is a widespread issue threatening marine biodiversity and coastal economies. Entanglements and ingestion are among the most common impacts of marine litter on wildlife. While most marine litter is assumed to come from land-based sources, marine items such as fishing gear tend to be responsible for most entanglement incidents. Entanglement is a frequent threat to pinniped species leading to suffering and potential death of affected individuals. I use a long-term dataset to investigate temporal trends in entanglement rates as well as to describe the most common material, type and probable source of entanglements of Cape fur seals (Arctocephalus pusillus pusillus) in the Victoria and Alfred (V&A) Waterfront and broader Cape Town harbour area. Between 1986-2018, 5843 entanglements (annual mean and standard deviation: 177±166) were recorded through systematic surveys, of which 5530 contained descriptive data relating to entanglement type. From 1994-2018 the number of seals checked, as well as the number of entangled seals were recorded. The mean entanglement rate, calculated as the total number of entanglements observed divided by the total number of seals checked, was 8% (range per year: 3–17%, n= 4488 entangled seals). This is the highest entanglement rate reported for a pinniped, albeit in a highly modified environment. Entanglement rates increased from 2007-2009, with a peak in 2009, and decreased to below 1990s levels in 2016. Significantly more seals were entangled in winter (rainy season) than in summer. Most entanglement items were made of plastic, with fishing line, rope and packing straps most commonly observed. The proportion of packing straps and rope decreased slightly in recent years, whereas the proportion of fishing line was relatively constant. Items associated with fishing and/or shipping activities accounted for 67% of entanglement cases, with fishing gear alone responsible for 33%. Offshore activities as well as the harbour itself were probable sources of most entanglement items, although a large storm drain that enters the harbour from central Cape Town probably also contributes to the problem. Key management interventions include education programmes targeting harbour employees and fishermen about the adverse impacts of marine litter, and implementing guidelines on appropriate waste disposal in the harbour. Putting up signage where seals commonly haul out highlighting the entanglement problem may also improve waste disposal habits. The V&A Waterfront is one of South Africa's leading tourist destinations and provides an opportunity to reach a large audience about the negative impacts of littering.